ANALISIS YURIDIS EKSEKUSI JAMINAN FIDUSIA UNTUK PERLINDUNGAN PARA PIHAK (STUDI KASUS PUTUSAN PENGADILAN TINGGI PEKANBARU PERKARA No. 36/PDT/2022/PT PBR jo No.242/Pdt.G/2021/PN.Btm) - Sahat Maruli Tua Tampubolon; Lagat Paroha Patar Siadari; Christiani Prasetiasari (Ensiklopedia of Journal, 2022)
Fiduciary Guarantee Law based on Law No. 42 of 1999 concerning Fiduciary Guarantee is the transfer of ownership rights to an object on the basis of trust provided that the object whose ownership rights are transferred remains in the control of the object's owner. Fiduciary guarantee is a form of guarantee institution based on jurisprudence that provides legal protection for the parties. Fiduciary guarantees have main characteristics, including facilitating execution in a simple, fast and low cost way according to the underlying rules. Fiduciary guarantees are evidenced by a fiduciary guarantee certificate which contains instructions "For Justice Based on the One Supreme Godhead" having the same executorial power as court decisions that have permanent legal force which can be implemented if the debtor is in default (default) through voluntary submission. The execution of the object of the fiduciary guarantee aims to pay off creditors' receivables. This study aims to analyze, examine and describe the executorial power of the fiduciary guarantee certificate in accordance with the procedures for the execution of the fiduciary guarantee object both on its own power and as a result of the execution without a court decision. For the sake of legal protection for the parties to the fiduciary agreement, the execution of the fiduciary guarantee must go through a court decision that has permanent legal force outside the procedure, which is a violation of the fiduciary guarantee law which is an unlawful act.Keywords:Execution, Fiduciary, Protection, the parties.